Developing a compositional style integrating Patah Lagu Melayu and western approach to music composition - Wan Mohd Syaril Annuar Wan Mohd Harith (Tanjong Malim, 2017)
Developing a compositional style integrating Patah Lagu Melayu and western approach to music composition by Wan Mohd Syaril Annuar Wan Mohd Harith